Acetylsalicylic acid is not associated with improved clinical outcomes after microsurgical breast reconstruction - Liu, Farrah; Miller, Travis J.; Henn, Dominic; Nguyen, Dung; Momeni, Arash (Journal of surgical research, 2023)
Introduction - Microvascular thrombosis with resultant flap loss remains a devastating complication in autologous breast reconstruction. While acetylsalicylic acid (ASA) for prevention of microvascular thrombosis is commonly administered postoperatively, clinical evidence supporting this practice remains insufficient. Here, we investigate the association of postoperative ASA administration with differences in clinical outcomes following microsurgical breast reconstruction. - Methods - A prospectively maintained database was queried to identify patients who had undergone microsurgical breast reconstruction. Patients were categorized based on whether they had received postoperative ASA for 30 d (Group 1) or had not received ASA (Group 2). Patient demographics, reconstructive outcomes, complications, and transfusion requirements were retrieved. - Results - One hundred thirty six patients with a mean age of 49.5 y and a mean body mass index of 28.5 kg/m2 who had undergone a total of 216 microsurgical breast reconstructions were included. No significant differences were noted with regard to patient demographics with the exceptions of increased rates of neoadjuvant chemotherapy and delayed reconstruction in Group 1. There were no significant differences in the rates of postoperative complications including breast hematoma, mastectomy skin flap necrosis, partial flap necrosis, seroma, and deep venous thrombosis between patients who did or did not receive ASA postoperatively. Similarly, no difference was noted regarding postoperative blood transfusion rates (Group 1: 9.9% versus Group 2: 9.1%; P = 0.78). Finally, patients in Group 1 had significantly longer hospital stays (Q1 = 4, median = 4.5, Q3 = 5). - Conclusions - Postoperative ASA administration is not associated with improved postoperative clinical outcomes. The use of ASA routinely after autologous breast reconstruction does not appear to be a necessity in practice.
Online veröffentlicht: 27. März 2023
Gesehen am 25.07.2023